TPACK Integration in Islamic Religious Education Learning: A Conceptual Model Based on Islamic Values in the Digital Era - Putri Nurhayati Lubis; Dewi Astuti (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2026)
The development of digital technology requires Islamic Religious Education (IRE) teachers to integrate technology, pedagogy, and content appropriately. Technological Pedagogical Content Knowledge (TPACK) provides an important framework for explaining such integration; however, its application in IRE presents a more complex challenge because IRE is oriented not only toward knowledge acquisition but also toward the development of attitudes, morality, manners, and Islamic values. This study aims to analyze the development and application of TPACK in IRE, identify its conceptual limitations, and formulate a conceptual model of TPACK based on Islamic values. The study employs a library research approach with an analytical literature review design. Relevant literature was analyzed through thematic analysis and narrative synthesis to identify the development of TPACK, its application in IRE, challenges in technology integration, developments in TPACK in the context of artificial intelligence and ethics, and the integration of Islamic values. The findings indicate that TPACK remains relevant as a foundation for integrating technology, pedagogy, and content, but it does not explicitly provide a value orientation for the use of technology in Islamic education. Based on this synthesis, the article proposes the TPACK-Tarbawi Model, which retains CK, PK, and TK as its core domains while positioning Islamic values as an orienting framework that guides technology selection, pedagogical design, content development, digital interaction, and learning evaluation. The model contributes conceptually by shifting the orientation of technology integration from merely technology integration toward contextual, ethical, and value-oriented integration in Islamic Religious Education.